Justification of the costs of forest reclamation of lands subject to desertification - Evgenia A. Korneeva (Siberian Journal of Life Sciences and Agriculture)
Background. In recent decades, environmental problems related to land degradation and depletion of soil cover have become especially acute in the south of Russia. The consequences of these threats are commonly referred to as desertification.